“No information was given concerning the origin of this torpedo”: A Soviet Weapon at the Canadian War Museum - Noakes, Jeff (The Northern Mariner / Le marin du nord, 2025)
Since 1960, the Canadian War Museum’s collection has included a Soviet torpedo whose history long remained obscure. Archival research has uncovered its 1951 transportation to Canada as part of a cargo of Soviet-made torpedoes and naval mines captured in North Korea, destined for analysis and training purposes. It has also revealed the intricacies and the implications of the technical analysis of the mines. This article examines the history of these weapons, and suggests some of the wider implications of their acquisition and analysis for the early Cold War Royal Canadian Navy, including potential areas for further research.